Forced compliance and its Relation to Hardness Personality for Educational Counselor (Journal of the College of Basic Education, 2026)
This research aimed to identify the level of forced compliance among educational counselors and to identify the rigidity of personality and the relationship between forced compliance and personal rigidity. To measure compliance among educational counselors, the researcher used the Atta scale (2023) while the kobasa scale (1979) was used to measure personal rigidity. The results revealed that the counselors showed a high level of forced compliance while they showed a low level of personal rigidity. It is worth noting that the study identified an inverse relationship between Forced compliance and personal rigidity .